ANALISIS WATAK DAN STRATEGI TOKOH PEREMPUAN DALAM DRAMA THE MERCHANT OF VENICE KARYA WILLIAM SHAKESPEARE - TOMASOA, HERLINA INGE (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
The William Shakespeareâ€™s drama namely The Merchant of Venice is choosen to be the focus of my discussion in this piece of writing which is later on specified into characters of the three female characters and their strategies in reaching their own goals. The objectives of this piece of writing are to identify, describe and analyzethe character as well as the strategies conducted by the female characters in this case Portia,Nerrisa and Jessica, the strategies to reach their goals in the drama. The writer applies Robertsâ€™ paradigm to indicate the characters of the female characters and stick to the definition of â€œstrategyâ€ by Sjahfrizal to analyze the strategy of Portia, Nerrisa and Jessica. The method used is descriptive. In terms of methodology three components become significant. Those are concept, paradigm, theory and methodof research. The concept deal with charactersâ€™ seeking process by Roberts and strategy by Sjahfrizal. Whereas in terms of analysing a descriptive method is applicable. The resultfindingsshow that there are some Â significanthuman characters found within the female characters such as brave, unselfish, wise, kind, trusty, loyal, smart, and so forth. Followed withstrategies namely planning arrangement, corporation, opportunity, and acting out to be different. Â Â Keywords: Character, Female, Strategy, Drama Â